Hormonal Contraceptive Use and History of Sexually Transmitted Infection as Risk Factors of the Pre‑Cancerous Cervical Lesions - Ni Made Parwati; I Wayan Gede Artawan Eka Putra; I Nyoman Mangku Karmaya (Universitas Udayana, 2015)
Background and purpose: Screening for pre-cancerous cervical lesions is already being implemented in Bali. This study aims to determine hormonal contraceptives and STI history as risk factors of pre-cancerous cervical lesions. Methods: A case-control study was conducted involving 76 women of childbearing age diagnosed with pre-cancerous cervical lesions who screened at two health centers in Denpasar Bali from January to March 2015. Control was 76 women of childbearing age with no pre-cancerous cervical lesions who screened at the same period. Consecutive sampling was used to select cases and controls. Data were collected through interview using questionnaires and analyzed using logistic regression to calculate adjusted odd ratio of each risk factor. Results: Multivariate analysis indicated that the use of hormonal contraceptives over ≥5 or <5 years increase risk of pre-cancerous cervical lesions with OR=10,7 (95%CI: 1,04-108,17) and OR=3,0 (95%CI: 1,16-7,84) compared to those who were not using hormonal contraception. History of sexually transmitted infections also increases risk of pre-cancerous cervical lesions with OR=9,7 (95%CI: 3,83 24,18). Conclusion: The use of hormonal contraceptives and history of sexual transmitted infections increased risks of pre-cancerous cervical lesions.